Implementasi Pengelolaan Alokasi Dana Desa (ADD) Sebagai Upaya Meningkatkan Kesejahteraan Masyarakat Desa Ngale, Kecamatan Paron, Kabupaten Ngawi - Puput Utami; Sudarmiani Sudarmiani; Dwi Nila Andriani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
This study aims to determine the implementation of Village Fund Allocation (ADD) management as an effort to improve the welfare of the people of Ngale Village, Paron District, Ngawi Regency. The studi was conducted on village heads, village heads, village officials, BPD, community with a total of 23 informants. The study was conducted in Ngale Village, Paron District, Ngawi Regency. The research method used is a qualitative method with the type of descriptive study research. Data collection through observation, interviews, documentation, and triangulation. The result showed that the management of the Village Fund Allocation (ADD) in Ngale Village was quite good, evindenced by the existence of plans for the use of the budget, the implementation of the stipulated program, admisnistration, reporting of program realization, and accountability. While the general welfare of the Ngale village is prosperous, there are a number of welfare indicators that have not been maximally met, such as income, consumption, and living conditions, different from the health services. The goverment efforts undertaken in an effort to improve the welfare of the people of Ngale Village is to do physical and non-physical development of the village.